THE ROLE OF YOUTH IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS: A COMPARATIVE ANALYSIS OF YOUTH IN INDIA AND INDONESIA - John, Sunil (Universitas Airlangga, 2024)
The interest in the youth and their contribution to the achievement of the SDG goals has increased in the recent times with academic research being undertaken by Governments to measure their role is a good sign towards creating opportunities for the young persons. Governments of India and Indonesia have taken a number of steps to encourage the youth to make a contribution to the achievement of the SDG goals especially those dealing with the eradication of poverty and gaining education and skills. In this article we will examine the measures taken by the governments to be compatible with the United Nations plan toaugment life and conditions of livelihood by 2030.